1992
DOI: 10.2172/6590696
|View full text |Cite
|
Sign up to set email alerts
|

Underground radionuclide migration at the Nevada Test Site

Abstract: This is an informal report intended primarily for internal or limited external distribution. Theopinionsand conclusions stated are those of the authorand may or may not be those of the Laboratory. Work performed under the auspices of the U.S. Department of Energy by the Lawrence Livermore National Laboratory under Contract W-7405-Eng-48.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 0 publications
1
33
0
Order By: Relevance
“…In ®eld studies where ground water can be eliminated as a possible transport mechanism, radionuclides were detected at a maximum of a few hundred metres from the original detonation point, and were attributed to gas movement through fractures, or fracture injection of vaporized material at detonation time 29,30 . The possibility that Pu from the Benham test site was blasted and deposited .1.3 km away, in two distinct aquifers separated by 300 m vertically and 30 m horizontally, seems highly unlikely.…”
mentioning
confidence: 99%
“…In ®eld studies where ground water can be eliminated as a possible transport mechanism, radionuclides were detected at a maximum of a few hundred metres from the original detonation point, and were attributed to gas movement through fractures, or fracture injection of vaporized material at detonation time 29,30 . The possibility that Pu from the Benham test site was blasted and deposited .1.3 km away, in two distinct aquifers separated by 300 m vertically and 30 m horizontally, seems highly unlikely.…”
mentioning
confidence: 99%
“…Although the reports of Nimz and Thompson (1992) and Smith et al (1996) would seem to support the colloidal transport scenario, the issue remains unresolved.…”
Section: Nevada Test Sitementioning
confidence: 99%
“…Results of these studies indicated that radionuclides were detectable at a maximum of a few hundred meters from the original detonation point (Nimz and Thompson 1992;Smith et al 1996). These radionuclides, including Pu would have been transported at the time of the original detonation by gas movement through fractures or fracture injection of vaporized material.…”
Section: Nevada Test Sitementioning
confidence: 99%
“…The enormous pressures generated during a nuclear test may create or enlarge preexisting fractures in the rock, injecting radioactive material considerable distances from the working point (Nimz and Thompson, 1992). Fractures may be vertical, subvertical, or horizontal.…”
Section: Underground Test Area Sitesmentioning
confidence: 99%